THE INFLUENCE OF HEDONIC LIFESTYLE AND EMOTIONAL INTELLIGENCE ON STUDENT FINANCIAL BEHAVIOR - Sindy Wahyuni; Habibburahman (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Today's lifestyle has become more dominant than just meeting basic needs. Most of the younger generation and college students spend money to fulfill their desires and pleasures by shopping without considering the benefits. This dynamic is influenced by environmental factors, both internal and external as well as technological advances. The purpose of this study is to analyze whether hedonic lifestyle and emotional intelligence are related to the financial behavior of FEB students of Bandar Lampung University (UBL). The sample in this study amounted to 72 students calculated by the Slovin formula. Data analysis is carried out through validity tests, reliability tests, descriptive statistics, multiple linear regression analysis, T tests, F tests, and coefficients of determination. The research findings explained that hedonic lifestyles did not significantly affect students' financial behavior, while emotional intelligence significantly influenced their financial behavior. Taken together or simultaneously, hedonic lifestyle and emotional intelligence have a significant effect on students' financial behavior.